Peranan Kompetensi Sumber Daya Manusia dalam Meningkatkan Kinerja UMKM (Studi Kasus pada Pelaku UMKM di Desa Kuala Dua, Kecamatan Sungai Raya, Kabupaten Kubu Raya) - Rani, Trisna Cahaya; Firayanti, Yuni; Mahardhika, Tubagus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study aims to determine the extent to which the role of human resource competency can improve the performance of MSMEs in Kuala Dua Village, Sungai Raya District, Kubu Raya Regency. The type of research used is qualitative with a case study approach. Data collection techniques in this study include interviews, observations, and documentation. In-depth interviews were conducted with 6 informants. Observations were made by directly observing MSME actors. Documentation involved taking several existing images. The results of this study indicate that business owners generally have good problem-solving skills, strive to maintain good relationships between employees and village officials, and are able to control and manage their businesses. The challenges faced in improving MSME performance through human resource competency in Kuala Dua Village include personal challenges such as workload, education, competitive market landscape, and work experience. Human resources in the village of Kuala Dua, some of them have never attended any training to improve their skills and abilities, either organized by government officials or certain agencies. Government officies may have held training, but it was not comprehensive to all aspects of the business.